Complexes of Monocationic Group 13 Elements with Pentaphospha‐ and Pentaarsaferrocene. Issue 13 (24th February 2014) - Fleischmann, Martin; Welsch, Stefan; Krauss, Hannes; Schmidt, Monika; Bodensteiner, Michael; Peresypkina, Eugenia V.; Sierka, Marek; Gröger, Christian; Scheer, Manfred
Abstract Reactions of the sandwich complexes [Cp*Fe(η5‐E5)] (Cp*=η5‐C5Me5; E=P (1), As (2)) with the monovalent Group 13 metals Tl+, In+, and Ga+ containing the weakly coordinating anion [TEF] ([TEF]=[Al{OC(CF3)3}4]−) are described. Here, the one‐dimensional coordination polymers [M(μ, η5:η1‐E5FeCp*)3]n[TEF]n (E=P, M=Tl (3 a), In (3 b), Ga (3 c); E=As, M=Tl (4 a), In (4 b)) are obtained as sole products in good yields. All products were analyzed by single‐crystal X‐ray diffraction, revealing a similar assembly of the products with η5‐bound E5 ligands and very weak σ‐interactions between one P or As atom of the ring to the neighbored Group 13 metal cation. By exchanging the [TEF] anion of 4 a for the larger [FAl] anion ([FAl]=[FAl{OC6F10(C6F5)}3]−), the coordination compound [Tl{(η5‐As5)FeCp*}3][FAl] (5) without any σ‐interactions of the As5‐ring is obtained. All products are readily soluble in CH2Cl2 and exhibit a dynamic coordination behavior in solution, which is supported by NMR spectroscopy and ESI‐MS spectrometry as well as by osmometric molecular‐weight determination. For a better understanding of the proceeding equilibrium DFT calculations of the cationic complexes were performed for the gas phase and in solution. Furthermore, the 31P{1H} magic‐angle spinning (MAS) NMR spectra of 3 a–c are presented and the first crystal structure of the starting material 2 was determined.